Evolution in Regional Planning: The Italian Path - De Luca, Guiseppe; Lingua, Valeria (ICONARCH International Congress of Architecture and Planning, 2014)
Focus of the paper are the models and practices of regional spatial planning activated in Italy in the most recent years, in order to evidence the innovation occurred and the challenges that regional planning institutions are facing. Compared to a theoretical and legislative framework that tends to separate the different types of regional planning (spatial, landscape, development planning), the experimental framework is characterized by pluralistic approaches in which a balance between a normative and a strategic nature of the territorial plan is searched, in order to introduce perspectives of economic and social development. In a continuous process of institutional reflexivity and learning, the regional institutions have now achieved that the notion of ’region’ has become more about social interaction than geographical location. For that, interesting experiences of intraregional and interregional cooperation are developing, as called Interregional table of Padano-Alpine-Maritime Macro Area in Northern Italy, a place-based approach generating supra-local shared visions that are of a certain interest.